GP16 Effect of droplet size on aerosol delivery during simulated neonatal mechanical ventilation. (June 2019) - Bennett, Gavin; Joyce, Mary; Fernández, Elena Fernández; MacLoughlin, Ronan
Abstract : Introduction: Invasive mechanical ventilation is a mainstay in neonatal intensive care and co-administration of aerosolised therapeutics is commonly prescribed. Considering their rapid breathing rate, low tidal volumes, small airways and interfaces, neonates present unique challenges for aerosol therapy. The objective of this study was to assess the effect of droplet size on aerosol delivery during simulated ventilation of a neonate. Methods: Simulated neonatal mechanical ventilation assessed the lung dose beyond the endotracheal tube (ETT) across two potential nebuliser placement positions within the circuit; at the dry side of the humidifier and between the Wye and ETT. 2 ml of 2 mg/ml salbutamol was nebulised using two vibrating mesh nebulisers (Aerogen Solo, Aerogen, Ireland) of varying droplet size (2.76µm and 4.30µm respectively). A vibrating mesh nebuliser was chosen as it does not add flow or pressure to the ventilator circuit. A neonatal ventilator (VN500, Dräger, Germany) (Vt 10mL, 60BPM, I:E ratio 1:2) in combination with a 2.5 mm ETT and humidified circuit was used. Lung dose was quantified after capturing aerosol on an absolute filter (RespirGard II 303, Baxter, Ireland) positioned between the ETT and test lung. The mass of drug eluted was determined using UV Spectrophotometry at 276nm. Results were expressed as a percentage of the nominal dose placed in the nebuliser medication cup. Results: Discussion: Increasing droplet size was associated with a significantly reduced lung dose when the nebuliser was positioned at the dry side of the humidifier (p-value = 0.02). Increasing droplet size was associated with a reduced lung dose when the nebuliser was placed between the Wye and ETT. However, this difference was not found to be statistically significant (p-value = 0.25). In conclusion, these findings demonstrate that droplet size affects aerosol delivery during neonatal mechanical ventilation.